Paste lithium metal negative electrode material as well as preparation method and application thereof

By preparing a paste-like lithium metal anode material, the problem of poor contact between the lithium metal electrode and the electrolyte interface in solid-state batteries was solved, thereby improving interface stability and electrochemical performance, reducing lithium-ion migration resistance, enhancing charge transfer kinetics, and avoiding lithium dendrite growth.

CN121011632APending Publication Date: 2025-11-25CHONGQING CHANGAN AUTOMOBILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511162791.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

In existing solid-state batteries, the poor contact between the lithium metal electrode and the electrolyte interface leads to high interfacial impedance and poor interfacial chemical-electrochemical stability, which affects the electrochemical performance.

Method used

A paste-like lithium metal anode material is used, which is composed of lithium powder, liquid alloy and surface tension modifier. Through specific mixing and processing, a paste with good plastic deformation ability and adhesion is formed, which is used for the preparation of anode sheets and reduces the charge transfer process of lithium ions at multiple phase interfaces.

Benefits of technology

It effectively reduces lithium-ion migration resistance, enhances interface stability, improves charge transfer kinetics, avoids lithium dendrite growth, and improves the electrochemical performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121011632A_ABST
    Figure CN121011632A_ABST
Patent Text Reader

Abstract

The invention discloses a paste lithium metal negative electrode material as well as a preparation method and application thereof, belongs to the technical field of solid-state batteries, and solves the problem that the overall electrochemical impedance of a solid-state battery of a lithium metal electrode in the prior art is large and the exertion of electrochemical performance is influenced. The paste lithium metal negative electrode material is characterized by comprising lithium powder, a liquid alloy and a surface tension regulator, the mass ratio of the lithium powder to the liquid alloy to the surface tension regulator is (0.5-7): (2-8.5): 1. The pasty lithium metal negative electrode material is pasty on the whole at room temperature or low temperature, has good plastic deformation capacity and relatively strong adhesive force, can effectively solve the problem of poor interface contact, effectively reduces the migration resistance and deposition potential energy of lithium ions, and enhances the stability of the interface; meanwhile, compared with an interface modification layer which is made of liquid alloy in the prior art, the charge transfer process of the lithium ions on multiple phase interfaces is avoided, and the lithium ion battery has better charge transfer dynamics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state battery technology, specifically to a paste-like lithium metal anode material, its preparation method, and its application. Background Technology

[0002] The new energy vehicle industry has experienced rapid development in recent years. As a core component of new energy vehicles, the market demand for power batteries has also seen explosive growth. However, current power batteries based on organic electrolytes are facing technological and industrial bottlenecks, making consumers increasingly eager for solid-state batteries with high energy density and high safety characteristics. Solid-state batteries use non-flammable solid electrolytes to replace the organic electrolytes in existing lithium-ion batteries, while also being compatible with higher energy density electrode materials. They are widely recognized as one of the best choices for eliminating current battery safety hazards and overcoming energy density bottlenecks.

[0003] The development of all-solid-state batteries based on high-capacity lithium metal electrodes (3860 mAh / g) represents the ultimate goal of solid-state battery research and development. However, their industrialization still faces a series of complex scientific and technological challenges, particularly in understanding and reconstructing the structure-property relationship of the lithium metal electrode-electrolyte interface. For example, poor interfacial contact, high interfacial impedance, poor interfacial chemical and electrochemical stability, and poor electrical contact stability due to lithium metal deposition and dissolution during charge and discharge processes directly limit the development and large-scale industrial application of high-energy-density solid-state batteries.

[0004] To address the issue of poor interfacial contact between the electrolyte and electrodes in solid-state batteries, which leads to unstable electrochemical performance, existing technologies employ a liquid metal layer as an interfacial buffer between the solid electrolyte and electrodes, effectively reducing the interfacial impedance. However, in these solutions, lithium ions must "cross" the liquid metal buffer layer during the electrochemical reaction, resulting in an increased number of electrochemical phase interfaces and consequently, an increase in the overall electrochemical impedance of the battery, severely impacting its electrochemical performance. Summary of the Invention

[0005] One objective of this invention is to provide a paste-like lithium metal anode material to solve the problem of high overall electrochemical impedance in solid-state batteries with lithium metal electrodes in the prior art, which affects the electrochemical performance. A second objective is to provide a method for preparing the paste-like lithium metal anode material. A third objective is to provide an anode sheet. A fourth objective is to provide a method for preparing the anode sheet. A fifth objective is to provide a solid-state battery.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] In a first aspect, this application provides a paste-like lithium metal anode material, comprising lithium powder, liquid alloy, and surface tension modifier;

[0008] The mass ratio of the lithium powder, liquid alloy and surface tension modifier is (0.5-7):(2-8.5):1.

[0009] In one possible implementation, the lithium powder has a particle size of 1–500 μm;

[0010] In one possible implementation, the lithium powder includes one or both of ordinary elemental lithium powder and surface-coated lithium powder;

[0011] In one possible implementation, the surface coating material of the surface-coated lithium powder includes one or more of Li2O, Li3N, Li2CO3, LiNO3, Al, Si, Mg, Sn, LiF, and LiCl;

[0012] In one possible implementation, the surface coating thickness of the surface-coated lithium powder is 20-150 nm.

[0013] In one possible implementation, the liquid alloy includes one or more of gallium-based liquid alloys and sodium-potassium alloys;

[0014] Optionally, the gallium-based liquid alloy is GaA, wherein A includes one or more of In, Sn, Al, Bi, Zn, Mg, and Ag; and the total mass percentage of A is 15-30% based on the mass of the gallium-based liquid alloy.

[0015] Optionally, the mass ratio of sodium to potassium in the sodium-potassium alloy is 1:(0.5-4).

[0016] In one possible implementation, the surface tension modifier includes one or more of acetylene black, conductive carbon black, Ketjen black, carbon nanotubes, graphite powder, graphene, graphene oxide, vapor-grown carbon fibers, silicon nanowires, hollow carbon nanospheres, polyaniline, polypyrrole, and polythiophene.

[0017] In one possible implementation, the mass ratio of lithium powder, liquid alloy and surface tension modifier is (2-7):(2-7):1, preferably (3-7):(2-6):1.

[0018] Secondly, this application provides a method for preparing a paste-like lithium metal anode material, wherein lithium powder, liquid alloy and surface tension modifier are mixed to obtain the paste-like lithium metal anode material.

[0019] In one possible implementation, the preparation method includes the following steps:

[0020] S1. The liquid alloy and the surface tension modifier are stirred and premixed for the first time to obtain a first premix;

[0021] S2. The lithium powder is mixed with the first premix for a second time to obtain the second premix.

[0022] Optionally, the stirring time for the first stirring is 5 to 20 minutes, and the stirring speed is 50 to 80 rpm;

[0023] Optionally, the stirring time for the second stirring is 5 to 20 minutes, and the stirring speed is 50 to 80 rpm;

[0024] Optionally, the surface tension modifier is vacuum dried before being mixed with the liquid alloy;

[0025] Optionally, the vacuum drying process is performed at a temperature of 50–120°C for 8–12 hours.

[0026] In one possible implementation, the preparation method further includes:

[0027] S3. Vacuum degassing and stirring of the second premix to obtain the paste-like lithium metal anode material;

[0028] Optionally, the stirring time for the vacuum degassing and stirring is 0.5h to 2h, and the stirring speed is 200 to 400rpm;

[0029] Optionally, the vacuum degree of the vacuum degassing and stirring is -60 to -90 kPa.

[0030] Thirdly, this application provides a negative electrode sheet, including the paste-like lithium metal negative electrode material or the paste-like lithium metal negative electrode material prepared according to the preparation method.

[0031] In one possible implementation, the negative electrode sheet includes a negative current collector and a paste-like lithium metal negative electrode material layer disposed on at least one side surface of the negative current collector;

[0032] In one possible implementation, the thickness of the paste-like lithium metal anode material layer is 0.1 μm to 3 mm;

[0033] In one possible implementation, the negative electrode current collector is selected from one of porous nickel foam mesh, porous copper foam mesh, porous stainless steel foam mesh, nickel foil, stainless steel foil, copper foil, titanium foil, composite copper foil, composite nickel foil, and polyimide-carbon nanotubes.

[0034] Thirdly, this application provides a method for preparing a negative electrode sheet, comprising: coating the paste-like lithium metal negative electrode material onto the surface of a negative electrode current collector to prepare a negative electrode sheet;

[0035] In one possible implementation, the coating method includes one or more of the following: doctor blade coating, roller coating, brush coating, spin coating, casting, screen printing, gravure printing, 3D printing, spraying, and inkjet printing.

[0036] Fifthly, this application provides a solid-state battery, including the aforementioned negative electrode sheet or a negative electrode sheet prepared according to the aforementioned method.

[0037] The beneficial effects of this invention are:

[0038] This application presents a paste-like lithium metal anode material comprising lithium powder, liquid alloy, and surface tension modifier; the mass ratio of the lithium powder, liquid alloy, and surface tension modifier is (0.5–7):(2–8.5):1. This paste-like lithium metal anode material exhibits a paste-like consistency at room temperature or low temperature, possessing excellent plastic deformation capability and strong adhesion. It effectively solves the problem of poor interfacial contact and continuously provides numerous deposition-dissolution sites for lithium atoms, effectively reducing lithium-ion migration resistance and deposition potential energy, and enhancing interfacial stability. Furthermore, compared to existing methods that use liquid alloy as an interfacial modification layer, this application avoids the lithium-ion transfer process at multiple phase interfaces, resulting in superior load transfer kinetics. Attached Figure Description

[0039] Figure 1 (a) is a liquid alloy state diagram, (b) is a paste lithium metal anode state diagram, and (c) is a scanning electron microscope image of the interface between the paste lithium metal anode material and the PEO-based solid electrolyte.

[0040] Figure 2 The graphs show the electrochemical deposition curves of the asymmetric electrode solid-state batteries of Example 1 and Comparative Examples 1 and 2 of the present invention.

[0041] Figure 3 The critical current density test diagrams are for the symmetrical electrode solid-state batteries in Embodiment 1 and Comparative Examples 1 and 2 of the present invention.

[0042] Figure 4 This is the first charge-discharge curve of the all-electrode solid-state battery constructed in Embodiment 1 of the present invention.

[0043] Figure 5 This is the cycle life curve of the all-electrode solid-state battery constructed in Embodiment 1 of the present invention.

[0044] Figure 6 This is the cycle life curve of the all-electrode solid-state battery constructed in Comparative Example 1 of the present invention.

[0045] Figure 7 This is the cycle life curve of the all-electrode solid-state battery constructed in Comparative Example 2 of the present invention. Detailed Implementation

[0046] The embodiments of the present invention will be described below with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention and not for limiting the scope of protection of the present invention.

[0047] In a first aspect, this application provides a paste-like lithium metal anode material, comprising lithium powder, liquid alloy, and surface tension modifier;

[0048] The mass ratio of the lithium powder, liquid alloy and surface tension modifier is (0.5-7):(2-8.5):1.

[0049] In the paste-like lithium metal anode material of this application, all component materials are uniformly distributed, wherein lithium powder serves as the active material; the surface tension modifier functions to regulate the interfacial properties of the liquid alloy phase. On the one hand, it helps the lithium powder micro-nano particles to be uniformly dispersed in the liquid metal phase, avoiding sedimentation or agglomeration; on the other hand, it makes the paste-like lithium metal anode material easier to wet and spread on the surface of a solid (electrolyte or current collector), resulting in a more uniform final coated electrode and increased interfacial contact. The liquid alloy phase serves as a carrier for the lithium powder and the surface tension modifier, and together they form a paste-like substance with plastic deformation capability and adhesion properties, such as... Figure 1 As shown in (a) and 1(b), lithium powder and surface tension modifier are uniformly distributed in the liquid alloy phase. The paste-like lithium metal anode material of this application is generally paste-like at room temperature or low temperature (-20℃), exhibiting good plastic deformation ability and strong adhesion. It effectively solves the problem of poor interfacial contact. The good interface provides a large number of sites for lithium atom deposition and dissolution, effectively reducing lithium-ion migration resistance and deposition potential energy, and enhancing interfacial stability, such as... Figure 1 (c) Meanwhile, compared with existing methods that use liquid alloys as interface modification layers, lithium ions in this application reduce the load transfer process at multiple phase interfaces and have better load transfer kinetics.

[0050] During the electrochemical dissolution process, lithium atoms near the electrolyte surface in the paste-like lithium metal anode material layer are first electrochemically extracted, forming a lithium-deficient phase interface or vacancies. However, due to the presence of the liquid alloy phase, it can spontaneously flow to fill the vacancies at the phase interface, ensuring interfacial contact. At the same time, under the influence of the concentration gradient and electric field, lithium atoms far from the interface layer will also spontaneously migrate to the interface, ensuring the integrity of the interfacial contact and enhancing interfacial kinetics.

[0051] In the electrochemical deposition process of the paste-like lithium metal anode material prepared by this invention, the deposited lithium atoms first nucleate and grow at the interface between the paste-like lithium metal anode material layer and the solid electrolyte, forming and generating electrochemical deposition stress. Since the solid electrolyte has high mechanical strength and the liquid phase alloy in the paste-like anode has fluidity, the anode can automatically adjust its shape to adapt to the changes in deposition stress, effectively dispersing the deposition stress and avoiding the growth of lithium dendrites towards the electrolyte side due to the inability to release deposition stress.

[0052] The application limits the amounts of lithium powder, liquid alloy, and surface tension modifier to a specific range, so that the paste-like lithium metal anode material has good plastic deformation ability and adhesion while maintaining a paste-like consistency.

[0053] In one possible implementation, the lithium powder has a particle size of 1–500 μm. Using lithium powder within the particle size range of this application can avoid agglomeration, improve dispersion uniformity, and ensure the cycle stability of the paste-like lithium metal anode material, which is a "quasi-elemental" component paste with uniform chemical and electrochemical properties.

[0054] In one possible implementation, the lithium powder includes one or both of ordinary elemental lithium powder and surface-coated lithium powder;

[0055] In one possible implementation, the particle size range of the ordinary elemental lithium powder is 1–100 μm;

[0056] In one possible implementation, the particle size of the surface-coated lithium powder ranges from 1 to 80 μm;

[0057] In one possible implementation, the surface coating material of the surface-coated lithium powder includes one or more of Li2O, Li3N, Li2CO3, LiNO3, Al, Si, Mg, Sn, LiF, and LiCl;

[0058] In one possible implementation, the surface coating thickness of the surface-coated lithium powder is 20–150 nm.

[0059] In one possible implementation, the liquid alloy includes one or more of gallium-based liquid alloys and sodium-potassium alloys;

[0060] In one possible implementation, the gallium-based liquid alloy is GaA, wherein A includes one or more of In, Sn, Al, Bi, Zn, Mg, and Ag; the total mass percentage of A is 15-30% based on the mass of the gallium-based liquid alloy, to ensure that the gallium-based liquid alloy is in liquid form.

[0061] In one possible implementation, the mass ratio of sodium to potassium in the sodium-potassium alloy is 1:(0.5-4).

[0062] The liquid alloy is completely liquid at room temperature.

[0063] In one possible implementation, the surface tension modifier includes one or more of acetylene black, conductive carbon black (SuperP), Ketjen black, carbon nanotubes (CNT), graphite powder, graphene, graphene oxide, vapor-grown carbon fiber (VGCF), silicon nanowires, hollow carbon nanospheres, polyaniline (PANI), polypyrrole (PPy), and polythiophene (PEDOT:PSS).

[0064] Secondly, this application provides a method for preparing the paste-like lithium metal anode material, wherein the lithium powder, liquid alloy and surface tension modifier are mixed to obtain the paste-like lithium metal anode material.

[0065] In one possible implementation, the preparation method includes the following steps:

[0066] S1. The liquid alloy and the surface tension modifier are stirred and premixed for the first time to obtain a first premix;

[0067] S2. The lithium powder is mixed with the first premix for a second time to obtain the second premix.

[0068] Liquid alloys have high surface tension and low viscosity. Mixing the liquid alloy with a surface tension modifier first, and then mixing it with lithium powder, can improve the uniformity of the mixture and ensure the accurate proportion of the paste material.

[0069] Optionally, the stirring time for the first stirring is 5 to 20 minutes, and the stirring speed is 50 to 80 rpm;

[0070] Optionally, the stirring time for the second stirring is 5 to 20 minutes, and the stirring speed is 50 to 80 rpm;

[0071] Optionally, the surface tension modifier is vacuum dried before being mixed with the liquid alloy;

[0072] Optionally, the vacuum drying process is performed at a temperature of 50–120°C for 8–12 hours.

[0073] In one possible implementation, the preparation method further includes S3, performing vacuum degassing and stirring on the second premix to obtain the paste-like lithium metal anode material; vacuum degassing can further remove bubbles, volatiles and tiny particles from the material.

[0074] Optionally, the stirring time for the vacuum degassing and stirring is 0.5h to 2h, and the stirring speed is 200 to 400rpm;

[0075] Optionally, the vacuum degree of the vacuum degassing and stirring is -60 to -90 kPa.

[0076] The method for preparing the paste-like lithium metal anode material of this application is simple and easy to operate, does not rely on special or complex process equipment, and is easy to industrialize. The prepared paste-like lithium metal anode material has good plastic deformation ability and strong adhesion, which facilitates further processing into anode sheets or direct application as anode coating on the electrolyte surface in solid-state batteries.

[0077] Thirdly, this application provides a negative electrode sheet, including the aforementioned paste-like lithium metal negative electrode material or the paste-like lithium metal negative electrode material prepared according to the aforementioned preparation method.

[0078] In one possible implementation, the negative electrode sheet includes a negative current collector and a paste-like lithium metal negative electrode material layer disposed on at least one side surface of the negative current collector;

[0079] In one possible implementation, the thickness of the paste-like lithium metal anode material layer is 0.1 μm-3 mm;

[0080] In one possible implementation, the negative electrode current collector is selected from one of porous nickel foam mesh, porous copper foam mesh, porous stainless steel foam mesh, nickel foil, stainless steel foil, copper foil, titanium foil, composite copper foil, composite nickel foil, and polyimide-carbon nanotubes (PI-CNTs).

[0081] Fourthly, this application provides a method for preparing a negative electrode sheet, comprising: coating the paste-like lithium metal negative electrode material onto the surface of a negative electrode current collector to prepare a negative electrode sheet.

[0082] In one possible implementation, the coating method includes one or more of the following: doctor blade coating, roller coating, brush coating, spin coating, casting, screen printing, gravure printing, 3D printing, spraying, and inkjet printing.

[0083] The negative electrode preparation method of the present invention is simple and easy to operate, does not depend on special or complex process equipment, and is suitable for continuous large-scale production.

[0084] Fifthly, this application provides a solid-state battery, including the aforementioned negative electrode sheet or a negative electrode sheet prepared according to the aforementioned method.

[0085] In one possible implementation, the solid-state battery further includes a positive electrode and a solid electrolyte;

[0086] In one possible implementation, the solid electrolyte comprises any one of the following: PEO-based polymer, PMMA-based polymer, PAN-based polymer, PVDF-based polymer, garnet-type structural oxide, NASICON-type structural oxide, LISICON-type structural oxide, perovskite-type oxide, thio-lisiCON-type sulfide, LGPS-type sulfide, glass-ceramic sulfide, and glassy sulfide.

[0087] In one possible implementation, the positive electrode sheet includes a positive current collector and a positive active material layer;

[0088] In one possible implementation, the positive electrode active material layer is a paste-like positive electrode active material layer.

[0089] In one possible implementation, the positive current collector is selected from Al foil, stainless steel foil, composite aluminum foil, composite stainless steel foil, and polyimide-carbon nanotubes (PI-CNTs).

[0090] The paste-like positive electrode active material layer is prepared by mixing positive electrode active material, conductive additives, ionic liquid, and lithium salt;

[0091] In one possible implementation, the positive electrode active material includes any one of ternary positive electrode active materials, quaternary positive electrode active materials, lithium iron phosphate, lithium cobalt oxide, and lithium-sulfur positive electrode active materials.

[0092] In one possible implementation, the conductive additive includes one or more of acetylene black, Super P, Ketjen black, and CNT;

[0093] In one possible implementation, the ionic liquid comprises one or more of 1-butyl-1-methylpyrrolidine bis(trifluoromethanesulfonyl)imide (PYR13TFSI, PY14TFSI or PY15TFSI);

[0094] In one possible implementation, the lithium salt includes one or both of LiTFSI and LiFSI;

[0095] In one possible implementation, the mass ratio of the positive electrode active material, conductive additive, ionic liquid and lithium salt is (4-7):1:(3.5-4):(0.5-1).

[0096] In one possible implementation, the positive electrode preparation process is carried out under inert atmosphere or low dew point conditions.

[0097] When assembling an asymmetric solid-state battery, a paste-like lithium metal anode material can be directly applied to the solid electrolyte side. Then, the asymmetric electrode type solid-state battery is formed by stacking the anode current collector, the solid electrolyte coated with the paste-like lithium metal anode material, and the cathode current collector in sequence, with the side of the solid electrolyte coated with the paste-like lithium metal anode material facing the cathode current collector.

[0098] When assembling a symmetrical solid-state battery, a paste-like lithium metal anode material can be directly applied to both sides of the solid electrolyte, and then the anode current collector, the solid electrolyte coated with the paste-like lithium metal anode material, and the anode current collector are stacked in sequence to form a symmetrical electrode type solid-state battery.

[0099] When assembling a full-electrode solid-state battery, a paste-like lithium metal anode material can be directly applied to one side of the solid electrolyte, and a paste-like cathode material can be directly applied to the other side of the solid electrolyte. Then, the cathode current collector, the solid electrolyte coated with the paste-like lithium metal anode material and the paste-like cathode material, and the cathode current collector are stacked sequentially to form a full-electrode solid-state battery. The side of the solid electrolyte coated with the paste-like lithium metal anode material faces the cathode current collector, and the side of the solid electrolyte coated with the paste-like cathode material faces the cathode current collector.

[0100] The preparation method of the PEO-based polymer solid electrolyte used in the following examples and comparative examples is as follows: PEO (Mw = 600,000) and lithium salt LiTFSI were weighed and dissolved in acetonitrile solvent (EO:Li). + The mixture (ratio 18:1) was thoroughly stirred until completely dissolved and poured into a smooth PTFE mold container. After thorough drying in a drying oven, the prepared PEO-based polymer solid electrolyte membrane was obtained. Testing showed that the thickness of the prepared PEO-based polymer solid electrolyte membrane was 68 μm, and its room temperature conductivity was 2.2 x 10⁻⁶. -4 S / cm.

[0101] Example 1

[0102] (1) This embodiment provides a method for preparing a paste-like lithium metal anode material, including the following steps:

[0103] S1. The liquid alloy and the surface tension regulator are stirred and premixed for the first time to obtain the first premix.

[0104] The mass ratio of liquid alloy to surface tension modifier is 40:10. The liquid alloy is a GaIn alloy, with a Ga:In mass ratio of 75.5:24.5. The surface tension modifier is acetylene black, which is vacuum dried at 100℃ for 12 hours before mixing. The first stirring time is 5 minutes, and the stirring speed is 60 rpm.

[0105] S2. The lithium powder and the first premix are stirred and premixed for a second time to obtain the second premix.

[0106] The lithium powder used is ordinary elemental lithium powder with a particle size range of 1–100 μm. The mass ratio of lithium powder, liquid alloy, and surface tension modifier is 50:40:10. The second stirring time is 5 min, and the stirring speed is 60 rpm.

[0107] S3. The second premix is ​​subjected to vacuum degassing and stirring to obtain a paste-like lithium metal anode material. The vacuum degassing and stirring time is 0.5 h, and the stirring speed is 350 rpm.

[0108] (2) This embodiment also provides a method for preparing a negative electrode sheet, including: coating the above-mentioned paste-like lithium metal negative electrode material onto a porous nickel foam mesh of negative electrode current collector, wherein the thickness of the paste-like lithium metal negative electrode material layer is 60 μm, thereby obtaining a negative electrode sheet.

[0109] (3) This embodiment also provides an asymmetric electrode type solid-state battery, including a negative electrode sheet, a PEO-based polymer solid electrolyte, and a positive electrode current collector Cu foil stacked in sequence. The negative electrode sheet has a side with a paste-like lithium metal negative electrode material facing the PEO-based polymer solid electrolyte.

[0110] (4) This embodiment also provides a symmetrical electrode type solid-state battery, including a negative electrode sheet, a PEO-based polymer solid electrolyte and a negative electrode sheet stacked in sequence. The negative electrode sheet has a side with a paste-like lithium metal negative electrode material facing the PEO-based polymer solid electrolyte.

[0111] (5) This embodiment also provides an all-electrode solid-state battery, the preparation method of which includes:

[0112] Preparation of the positive electrode sheet:

[0113] First, 0.3 mol of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 1 L of ionic liquid PY14TFSI to form a homogeneous solution (density approximately 1.47 mg / μL). Then, 145 μL of this homogeneous solution was added to a pre-mixed mixture of lithium iron phosphate cathode material (240 mg, LFP) and conductive carbon black Super-P (80 mg). After thorough grinding, the mixture was dried in a vacuum oven at 60 °C for 24 hours to obtain a paste-like cathode active material, which was then transferred to a glove box for storage. The paste-like cathode active material was then coated onto an Al foil, with a loading of approximately 2.5 mg / cm³. 2 The thickness is approximately 120 μm. A positive electrode sheet is obtained.

[0114] A full-electrode solid-state battery is constructed by sequentially stacking the negative electrode, PEO-based polymer solid electrolyte, and positive electrode.

[0115] Example 2

[0116] This embodiment provides a method for preparing a paste-like lithium metal anode material, which is basically the same as that in Example 1, except that the mass ratio of lithium powder, liquid alloy, and surface tension modifier is 30:60:10.

[0117] This embodiment also provides a method for preparing a negative electrode sheet, which is the same as in Embodiment 1.

[0118] This embodiment also provides a symmetrical electrode type solid-state battery, which is assembled in the same way as in Embodiment 1.

[0119] Example 3

[0120] This embodiment provides a method for preparing a paste-like lithium metal anode material, which is basically the same as that in Example 1, except that the mass ratio of lithium powder, liquid alloy, and surface tension modifier is 40:50:10.

[0121] This embodiment also provides a method for preparing a negative electrode sheet, which is the same as in Embodiment 1.

[0122] This embodiment also provides a symmetrical electrode type solid-state battery, which is assembled in the same way as in Embodiment 1.

[0123] Example 4

[0124] This embodiment provides a method for preparing a paste-like lithium metal anode material, which is basically the same as that in Example 1, except that the mass ratio of lithium powder, liquid alloy, and surface tension modifier is 55:35:10.

[0125] This embodiment also provides a method for preparing a negative electrode sheet, which is the same as in Embodiment 1.

[0126] This embodiment also provides a symmetrical electrode type solid-state battery, which is assembled in the same way as in Embodiment 1.

[0127] Example 5

[0128] This embodiment provides a method for preparing a paste-like lithium metal anode material, which is basically the same as that in Example 1, except that the mass ratio of lithium powder, liquid alloy, and surface tension modifier is 60:30:10.

[0129] This embodiment also provides a method for preparing a negative electrode sheet, which is the same as in Embodiment 1.

[0130] This embodiment also provides a symmetrical electrode type solid-state battery, which is assembled in the same way as in Embodiment 1.

[0131] Example 6

[0132] This embodiment provides a method for preparing a paste-like lithium metal anode material, which is basically the same as that in Example 1, except that the surface tension modifier is vapor-grown carbon fiber (VGCF).

[0133] This embodiment also provides a method for preparing a negative electrode sheet, which is the same as in Embodiment 1.

[0134] This embodiment also provides a symmetrical electrode type solid-state battery, which is assembled in the same way as in Embodiment 1.

[0135] Example 7

[0136] This embodiment provides a method for preparing a paste-like lithium metal anode material, which is basically the same as that in Example 1, except that the lithium powder is a surface-coated lithium powder with a particle size range of 1 to 80 μm, and the coating material is Li2O with a coating thickness of 50 nm.

[0137] This embodiment also provides a method for preparing a negative electrode sheet, which is the same as in Embodiment 1.

[0138] This embodiment also provides a symmetrical electrode type solid-state battery, which is assembled in the same way as in Embodiment 1.

[0139] Example 8

[0140] This embodiment provides a method for preparing a paste-like lithium metal anode material, which is basically the same as that in Example 1, except that the liquid alloy is a NaK alloy, wherein the mass ratio of Na to K is 1:1.

[0141] This embodiment also provides a method for preparing a negative electrode sheet, which is the same as in Embodiment 1.

[0142] This embodiment also provides a symmetrical electrode type solid-state battery, which is assembled in the same way as in Embodiment 1.

[0143] Comparative Example 1

[0144] This comparative example provides a negative electrode sheet, including a porous nickel foam mesh as a negative electrode current collector and a pure lithium metal foil with a thickness of 60 μm.

[0145] This comparative example also provides a method for preparing a negative electrode sheet, comprising: bonding the above-mentioned pure metallic lithium foil negative electrode material onto a porous foam nickel mesh of a negative electrode current collector to obtain a negative electrode sheet.

[0146] This comparative example also provides an asymmetric electrode type solid-state battery, which is assembled in the same way as in Example 1.

[0147] This comparative example also provides a symmetrical electrode type solid-state battery, which is assembled in the same way as in Example 1.

[0148] This comparative example also provides an all-electrode solid-state battery, which is assembled in the same way as in Example 1.

[0149] Comparative Example 2

[0150] This comparative example provides an asymmetric electrode type solid-state battery, which is basically the same as the asymmetric electrode type solid-state battery of Comparative Example 1. The difference is that a liquid alloy modification layer is provided between the negative electrode sheet and the PEO-based polymer solid electrolyte. The thickness of the liquid alloy layer is about 8 μm (the composition of the liquid alloy is the same as that of Example 1).

[0151] This comparative example also provides a symmetrical electrode solid-state battery, which is basically the same as the symmetrical electrode solid-state battery of Comparative Example 1. The difference is that a liquid alloy modification layer (the composition of the liquid alloy is the same as that of Example 1) is provided between the two negative electrode plates and the PEO-based polymer solid electrolyte.

[0152] Test case

[0153] The batteries prepared in each embodiment and comparative example were stored in a 60°C incubator for 6 hours to further promote interfacial contact fusion, and then their performance was tested. All tests were conducted at 60°C.

[0154] (1) Performance testing of asymmetric electrode type solid-state batteries

[0155] The prepared asymmetric electrode solid-state battery was encapsulated in a coin cell casing, and then an electrochemical dissolution test was performed: the dissolution current density was 0.1 mA / cm². 2 The deposition time was 1 hour.

[0156] The highest deposition potential of the asymmetric electrode solid-state battery was measured, and the test results are shown in [link to test results]. Figure 2 See Table 1.

[0157] Table 1 Performance of Asymmetric Electrode Solid-State Batteries

[0158]

[0159] Combination Figure 2 As shown in Table 1, firstly, compared to batteries composed of pure lithium metal foil and lithium metal modified with liquid alloy, the asymmetric electrode type solid-state battery composed of the paste-like lithium metal anode of this application has the lowest total impedance. This indicates that the contact state at the paste-like lithium metal anode-PEO solid electrolyte interface is significantly better than the other two cases. This is consistent with... Figure 1 (c) The results observed by SEM show a completely tight contact at the interface; secondly, the asymmetric electrode type solid composed of the paste-like lithium metal anode of this application exhibits lower electrochemical dissolution potential and electrochemical polarization potential, indicating that the paste-like lithium metal anode has high electrochemical activity and good lithium transport kinetics, which can ensure continuous and stable contact at the interface and is beneficial for suppressing battery short circuits. The above experimental results show that the paste-like lithium metal anode of this invention has good lithium dissolution electrochemical activity and lithium dissolution kinetics.

[0160] (2) Performance testing methods for symmetrical electrode type solid-state batteries

[0161] The prepared symmetrical electrode solid-state battery was encapsulated in a coin cell, and then electrochemical impedance spectroscopy and critical current density tests were performed sequentially. Electrochemical impedance spectroscopy test: frequency range 0.1Hz-10 Hz. 6 Hz, amplitude 10mV. Critical current density test: deposition / dissolution time was 1h, current density was 0.1mA / cm². 2 The current density was increased incrementally, with each current density cycled 5 times. All tests were conducted at 60°C. Relevant test results can be found... Figure 3 And Table 2.

[0162] Table 2 Performance of Symmetric Electrode Solid-State Batteries

[0163]

[0164]

[0165] As shown in Table 2, when the mass fraction of lithium powder is ≤50%, the interfacial impedance of the symmetrical electrode solid-state battery remains at approximately 21 Ω·cm. 2This indicates that under these conditions, the paste-like lithium metal anode-solid electrolyte interface has achieved complete contact. However, the critical current density test results show that the critical current density of the symmetrical battery gradually increases with the increase of the lithium powder mass fraction, indicating an improvement in the current tolerance of the symmetrical battery. This is because when the active component in the paste anode is relatively small, the migration path of lithium atoms in the paste electrode will increase accordingly, and the kinetics will be affected to a certain extent, thus affecting the magnitude of the critical current density. When the lithium powder mass fraction is >50%, the interfacial impedance of the symmetrical electrode type solid battery shows an upward trend with the increase of the mass ratio of lithium metal powder in the paste-like lithium metal anode, from 21 Ω·cm. 2 Increased to 47.8 Ω·cm 2 Meanwhile, the critical current density of the symmetrical cell increased from 0.7 mA / cm². 2 It decreased to 0.3 mA / cm 2 This is because as the content of lithium metal powder increases, the microstructure and physical properties of the negative electrode are altered, which in turn affects the chemical activity and interfacial transport properties of the paste lithium metal, increasing the resistance to ion transport at the interface and increasing the risk of short circuits.

[0166] Combine Table 2 and Figure 3 It is known that, compared with pure lithium metal and lithium metal interfaces modified with liquid alloys, the paste-like lithium metal anode exhibits lower interfacial impedance and higher critical current density in symmetrical electrode solid-state batteries. The above experimental results show that the paste-like lithium metal anode of the present invention is more conducive to reducing interfacial impedance, suppressing short circuits, and improving the electrochemical stability and current resistance of the battery. On the other hand, it also shows that, compared with the lithium metal-solid electrolyte interface modified with liquid alloys, in the paste-like lithium metal anode of the present application, lithium ions do not need to "cross" the liquid metal buffer layer during the electrochemical reaction, reducing the electrochemical phase interface, and its transport kinetics are better, thus possessing higher critical current resistance.

[0167] The results in Table 2 also show that adjusting the component materials within the scope of the claim has the same effect, indicating that this application has high applicability.

[0168] (3) Performance testing of all-electrode solid-state batteries

[0169] The prepared all-electrode solid-state battery was encapsulated in a coin cell. Impedance testing was performed on the prepared all-electrode solid-state battery, followed by cycle testing. Impedance test parameters were maintained consistent with those of the pre-symmetric battery. Cyclic testing was conducted at a rate of 0.5C. All tests were performed at 60℃. Test results are shown below. Figures 4-7 And Table 3.

[0170] Table 3 Performance of All-Electrode Solid-State Batteries

[0171]

[0172]

[0173] From Table 3 and Figures 4-7 It can be seen that the all-electrode solid-state battery assembled from paste-like lithium metal anode material has the lowest impedance, indicating that the paste-like lithium metal material has a significant effect on improving the interface. (Comparison) Figure 5-7 As shown in Table 3, the paste lithium metal material has the highest capacity retention and high cycling stability, indicating that the paste lithium metal can maintain good interfacial contact and stable electrochemical properties during long-term cycling.

[0174] The above embodiments are merely preferred embodiments provided to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention.

Claims

1. A paste-like lithium metal anode material, characterized in that, Including lithium powder, liquid alloys, and surface tension modifiers; The mass ratio of the lithium powder, liquid alloy and surface tension modifier is (0.5-7):(2-8.5):

1.

2. The paste-like lithium metal anode material according to claim 1, characterized in that, The lithium powder has a particle size of 1–500 μm; Optionally, the lithium powder includes one or both of ordinary elemental lithium powder and surface-coated lithium powder; Optionally, the surface coating material of the surface-coated lithium powder includes one or more of Li2O, Li3N, Li2CO3, LiNO3, Al, Si, Mg, Sn, LiF, and LiCl; Optionally, the thickness of the surface coating layer of the surface-coated lithium powder is 20–150 nm.

3. The paste-like lithium metal anode material according to claim 1, characterized in that, The liquid alloy includes one or more of gallium-based liquid alloys and sodium-potassium alloys; Optionally, the gallium-based liquid alloy is GaA, wherein A includes one or more of In, Sn, Al, Bi, Zn, Mg, and Ag; and the total mass percentage of A is 15-30% based on the mass of the gallium-based liquid alloy. Optionally, the mass ratio of sodium to potassium in the sodium-potassium alloy is 1:(0.5-4).

4. The paste-like lithium metal anode material according to claim 1, characterized in that, At least one of the following conditions must be met: (1) The surface tension modifier includes one or more of the following: acetylene black, conductive carbon black, Ketjen black, carbon nanotubes, graphite powder, graphene, graphene oxide, vapor-grown carbon fibers, silicon nanowires, hollow carbon nanospheres, polyaniline, polypyrrole, and polythiophene. (2) The mass ratio of lithium powder, liquid alloy and surface tension modifier is (2-7):(2-7):1, preferably (3-7):(2-6):

1.

5. A method for preparing the paste-like lithium metal anode material according to any one of claims 1-4, characterized in that, The lithium powder, liquid alloy, and surface tension modifier are mixed to obtain the paste-like lithium metal anode material.

6. The method for preparing the paste-like lithium metal anode material according to claim 5, characterized in that, The preparation method includes the following steps: S1. The liquid alloy and the surface tension modifier are stirred and premixed for the first time to obtain a first premix; S2. The lithium powder is mixed with the first premix for a second time to obtain the second premix. Optionally, the stirring time for the first stirring is 5 to 20 minutes, and the stirring speed is 50 to 80 rpm; Optionally, the stirring time for the second stirring is 5 to 20 minutes, and the stirring speed is 50 to 80 rpm; Optionally, the surface tension modifier is vacuum dried before being mixed with the liquid alloy; Optionally, the vacuum drying process is performed at a temperature of 50–120°C for 8–12 hours.

7. The method for preparing the paste-like lithium metal anode material according to claim 6, characterized in that, Also includes: S3. Vacuum degassing and stirring of the second premix to obtain the paste-like lithium metal anode material; Optionally, the stirring time for the vacuum degassing and stirring is 0.5h to 2h, and the stirring speed is 200 to 400 rpm; Optionally, the vacuum degree of the vacuum degassing and stirring is -60 to -90 kPa.

8. A negative electrode sheet, characterized in that, Includes the paste-like lithium metal anode material according to any one of claims 1-4 or the paste-like lithium metal anode material prepared by the preparation method according to any one of claims 5-7; Optionally, the negative electrode sheet includes a negative current collector and a paste-like lithium metal negative electrode material layer disposed on at least one side surface of the negative current collector; Optionally, the thickness of the paste-like lithium metal anode material layer is 0.1 μm to 3 mm; Optionally, the negative electrode current collector is selected from one of porous nickel foam mesh, porous copper foam mesh, porous stainless steel foam mesh, nickel foil, stainless steel foil, copper foil, titanium foil, composite copper foil, composite nickel foil, and polyimide-carbon nanotubes.

9. A method for preparing the negative electrode sheet according to claim 8, characterized in that, include: The paste-like lithium metal anode material is coated onto the surface of the anode current collector to prepare an anode sheet. Optionally, the coating method includes one or more of the following: doctor blade coating, roller coating, brush coating, spin coating, casting, screen printing, gravure printing, 3D printing, spraying, and inkjet printing.

10. A solid-state battery, characterized in that, This includes the negative electrode sheet as described in claim 8 or the negative electrode sheet prepared by the method described in claim 9.